Algas perifíticas sobre substrato artificial e natural no rio do Corvo (tributário do reservatório de Rosana) : composição, abundância, biomassa e produtividade. - Felisberto, Sirlene Aparecida (2007)
Cap.1: This paper aimed to study the composition and species richness of periphytic algae in response to the time of colonization on artificial and natural substratum in a tropical reservoir. Egeria najas as used as natural substratum and plastic plant as artificial. This experiment was accomplished in the Corvo River, tributary of the Rosana reservoir (Paranapanema basin). The samplings were accomplished in the period from 21 November to 12 December 2003. This period is characterized as hot and rainy. The changes in the species composition in artificial substratum were analyzed using the Jaccard similarity and beta diversity indices. Composition and species richness didn't different in the two substrata. 495 taxa were registered in the phycoperiphytic community, distributed in 133 genera and 11 classes. Zygnemaphyceae presented higher species number, following for Bacillariophyceae, Chlorophyceae and Cyanophyceae, in both substrata. Staurodesmus, Closterium, Staurastrum and Cosmarium (Desmidiales); Gomphonema and Eunotia (Penales); Characium, Scenedesmus and Desmodesmus (Chlorococcales) were the most specious genera, independent of the substratum type. Among the growth forms, not flagelad unicellular algae dominated the assemblies of the two substrata. The results of the beta diversity, in general, demonstrated that artificial substratum presented a tendency of higher substitution of species in the 3ª week. The epiphytic community reached higher richness and species diversity in the 15th sucessional day. This fact was demonstrated in the dendrograma of the similarity analysis, where 15th day differentiated of the other days. Species richness, independent of the substratum type was probably related the higher nutrients and turbidity values, as well as action of wind and rainfall.